2018
DOI: 10.1016/j.bbadis.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal α-tocopherol overload programs alterations in kidney development and renal angiotensin II signaling pathways at birth and at juvenile age: Mechanisms underlying the development of elevated blood pressure

Abstract: α-Tocopherol (α-Toc) overload increases the risk of dying in humans (E.R. Miller III et al. Meta-analysis: high-dosage vitamin E supplementation may increase all-cause mortality Ann Int Med. 142 (2005) 37-46), and overload during early development leads to elevation of blood pressure at adult life, but the mechanism(s) remains unknown. We hypothesized that α-Toc overload during organogenesis affects the renal renin angiotensin system (RAS) components and renal Na handling, culminating with late elevated blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The accentuated decrease in cardiac and renal indexes provoked by α‐Tocopherol, especially when given during lactation, regardless of whether the offspring was programmed by saline overload or not (Figure B,C), suggests that it impairs organ development and maturation in early life. This idea, with regard to the kidney, is supported by histological data showing that the vitamin retards nephrogenesis when administered during gestation, an effect accompanied by altered local Ang II in 1‐day‐old pups . Decrease in renal mass is also considered indicative of compromised renal development in humans, with an accelerated progression of renal lesions .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The accentuated decrease in cardiac and renal indexes provoked by α‐Tocopherol, especially when given during lactation, regardless of whether the offspring was programmed by saline overload or not (Figure B,C), suggests that it impairs organ development and maturation in early life. This idea, with regard to the kidney, is supported by histological data showing that the vitamin retards nephrogenesis when administered during gestation, an effect accompanied by altered local Ang II in 1‐day‐old pups . Decrease in renal mass is also considered indicative of compromised renal development in humans, with an accelerated progression of renal lesions .…”
Section: Discussionmentioning
confidence: 94%
“…Inhibition of RAS for short periods is sufficient to decrease blood pressure in SHR, as well as to the recovery of the normal activities of Na + ‐transporting ATPases in the renal proximal tubule and the control values of creatinine clearance (CrCl) in the offspring from mothers given salt overloading during gestation . A central role for RAS in the cardiovascular and renal effects of α‐Tocopherol received support in one of our studies, in which we demonstrated that maternal α‐Tocopherol during gestation programs retarded renal development in the pups (enlargement of the nephrogenic zone in kidneys of 1‐day‐old pups), as well as for altered expression of several components of the local renin/angiotensin system in both pups and juvenile rats (upregulation of Ang II receptors (AT 1 R and AT 2 R) and of several isoforms of PKC, a key element of AT 1 R‐linked signalling pathways) . We had previously shown that α‐Tocopherol given by gavage during lactation increases the number of cells that are positive for angiotensin II (Ang II) in the kidneys of young adult rats …”
Section: Introductionmentioning
confidence: 80%
“…But all tested antibodies gave signals in tissues from AT1A knock-out mice and nontransfected 4B cells. Despite this first report of aspecificity, the sc-1173 antibodies were still widely used in the literature up to now (Rizzetti et al 2018;Zhao et al 2018;Ribeiro et al 2018) and it has just been discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies targeting both angiotensin II (AngII) receptors type 1 (AT1) and type 2 (AT2) have been described as non-specific (Benicky et al 2012;Herrera et al 2013;Hafko et al 2013). Despite these findings, antibodies directed against AT1 receptors are still widely used in the literature with more than twenty publications in 2017 using the Santa Cruz aspecific sc-1173 polyclonal antibodies (Chao et al 2017;Young et al 2017;Liu et al 2017) and already five publications in 2018 (Ahad et al 2018;Ishikane et al 2018;Rizzetti et al 2018;Zhao et al 2018;Ribeiro et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…RIPA buffer supplemented with a protease inhibitor cocktail was used for homogenization of the tissue at a ratio of 1 g kidney to 7 mL of solution. Superoxide anion (O 2 -) generation was assessed using the lucigenin-enhanced chemiluminescence method, as previously described 19 .…”
Section: Basal and Nadph Oxidase-dependent Superoxide Anion Levels Inmentioning
confidence: 99%